Flow Cytometry–Based Cytotoxicity and Antibody Binding Assay. Issue 1 (16th February 2018) - Alheim, Mats
Abstract: Human leukocyte antigen (HLA) antibodies with the ability to activate complement are associated with an increased risk of early antibody‐mediated graft rejection in kidney transplantation (KTx). Detection of these potentially harmful complement‐fixing HLA antibodies is commonly performed via the complement‐dependent cytotoxicity (CDC) assay according to protocols that were developed as early as 40 years ago. The read‐out for this assay is based on manual scoring by visual inspection of cells under a fluorescence microscope. CDC is often used in combination with the flow cytometry–based lymphocyte crossmatch assay (FCXM), which, with high sensitivity, detects HLA antibody binding. Here we describe a new approach wherein both cytotoxicity and antibody binding can be simultaneously assessed with flow cytometry. Two strategies are described, using either magnetic bead–enriched T and B lymphocytes or bulk peripheral blood mononuclear cells (PBMC) as donor target cells. Curr. Protoc. Cytom . 66:6.34.1‐6.34.11. © 2013 by John Wiley & Sons, Inc.